Fibrosis in canine transmissible venereal tumor after chemotherapy with vincristine - do Prado Duzanski, Anderson [UNESP]; Feo, Haline Ballestero [UNESP]; Flórez, Luis Mauricio Montoya; Dinau, Fernando Carmona [UNESP]; Paiva, Bruna Ribeiro [UNESP]; Brandão, Cláudia Valéria Seullner [UNESP]; Rocha, Noeme Sousa [UNESP] (Revista Brasileira de Medicina Veterinaria, 2023)
The canine transmissible venereal tumor is type of transmissible cancer that occurs naturally through allogenic cellular transplants. Commonly diagnosed in the genital area of sexually active dogs, the tumor typically responds well to vincristine sulfate chemotherapy, although there are cases of resistance to the drug correlated with the tumoral phenotype. We describe herein a case of fibrosis in an area affected by the tumor in a dog after vincristine chemotherapeutic treatment that was associated with an idiosyncratic reaction to the drug.
Keywords: CTVT; dog; fibrosis; idiosyncratic reaction; vincristine